Five-year results of brentuximab vedotin in patients with relapsed or refractory systemic anaplastic large cell lymphoma - Pro, Barbara; Advani, Ranjana; Brice, Pauline; Bartlett, Nancy L; Rosenblatt, Joseph D; Illidge, Tim; Matous, Jeffrey; Ramchandren, Radhakrishnan; Fanale, Michelle; Connors, Joseph M; Fenton, Keenan; Huebner, Dirk; et al. (Blood, 2017)
This pivotal phase 2 study evaluated the safety and efficacy of brentuximab vedotin in patients with relapsed or refractory (R/R) systemic anaplastic large cell lymphoma (ALCL). After a median observation period of approximately 6 years from first treatment, we examined the durability of remission, progression-free survival (PFS), overall survival (OS), and safety outcomes of patients treated on this trial. Among all enrolled patients (n = 58), no progressions were observed beyond 40 months, and median OS was not reached. Patients with a complete response (CR), as assessed by the investigator (38 of 58, 66%), continued to demonstrate improved outcomes with neither median OS nor PFS reached. Of the 38 CR patients, 16 received a consolidative stem cell transplant (SCT) with median PFS not reached. Among patients who were on-study and in remission at study closure, 16 patients had not received any new treatment after single-agent brentuximab vedotin other than consolidative SCT. Among this subset of 16 patients, 8 received SCT, and the remaining 8 patients (14% of all enrolled patients) remained in sustained remission without consolidative SCT or any new anticancer therapy. Thirty-three patients experienced peripheral neuropathy, among whom, the majority (30 of 33, 91%) had experienced resolution or improvement at their last assessment. These final results, which demonstrated a high rate of peripheral neuropathy resolution, and durable remissions in a subset of patients with relapsed or refractory systemic ALCL, provide evidence that single-agent brentuximab vedotin may be a potentially curative treatment option. This trial was registered at www.clinicaltrials.gov as #NCT00866047.